Front of the vulnerability of elderly HIV/aids: current trends of scientific production in Brazil - Garcia, Giulianna S.; Lima, Lorrayne F.; Silva, Jeferson B.; Andrade, Luciana D.F.; Abrão, Fatima Maria S. (Brazilian Journal of Sexually Transmitted Diseases, 2012)
Introduction: senility is considered a phase of great vulnerability to HIV infection; this is due to the insertion of the biopsychosocial context of the elderly, in which there is usually a combination of figure losses, limitations, inability to procreation and sexual inactivity. Objective: to identify trends in scientific production about the factors that increase the vulnerability of the elderly to Acquired Immunodeficiency Syndrome (AIDS). Methods: this is a study of integrative review, conducted by consulting the Virtual Health Library (VHL), and used the databases: Scientific Electronic Library Online (SciELO) and Latin American and Caribbean Health Sciences (LILACS). Were consulted articles covering the period from 2008 to 2012, and they were organized in a specific table and analyzed for data description. Results: several determinants of vulnerability to HIV/AIDS in the elderly were identified in the studies, and almost all of them were the input of our work, among the most commonly found in the readings taken are: existence of taboos about sexuality in old age and little knowledge the elderly about HIV infection. Conclusion: the method used was effective for realization of our goals. The results presented throughout the review shows that there are still many taboos concerning sexuality of the elderly, and consequently few clarifications on prevention, transmission and other issues surrounding AIDS.